Becoming Educational Advocates: Experience-based Tips. (July 2015) - Dresser, Rocío; Mathur, Ravisha
This article deals with the importance of building partnerships between legislators and educators in order to impact educational legislation. To this end, the faculty in the college of education at a large, urban university made institutional changes to establish a proactive relationship amongst stakeholders. As a result of this exchange, we were able to impact two important legislative bills, Assembly Bill (AB) No. 1871 on bilingual teacher credentialing and the State Seal of Biliteracy (SSB). The AB No. 1871 authorized multiple paths to a bilingual teaching certification. The Biliteracy seal, effective from 1 January 2012, recognizes secondary school graduates who have achieved a high level of proficiency in speaking, reading and writing in one or more languages in addition to English. In the latter part of the article, we share valuable tips for educators who wish to engage in local and national advocacy.